Temperature-Related Bioclimatic Variables Play a Greater Role in the Spatial Distribution of Bumblebee Species in Northern Pakistan - Muhammad Naeem; Arzoo Rani; Weiyao Lyu; Huaibo Zhao; Maryam Riasat; Saail Abbas; Sabir Hussain; Nawaz Haider Bashir; Qiang Li; Huanhuan Chen (Insects)
Bumblebee species are vital wild pollinators, providing essential pollination services for various crops, fruits, and vegetables. However, their biodiversity is vulnerable to decline due to climate change, particularly in regions like northern Pakistan. Despite this, no research has yet been conducted on the distribution patterns of bumblebee species in this region. The current study aimed to model the spatial distribution of three important bumblebee species: Bombus haemorrhoidalis, B. rufofasciatus, and B. subtypicus in northern Pakistan. Habitat suitability and the contribution of bioclimatic variables to the spatial distribution of species were assessed using the MaxEnt approach. Current and future bioclimatic variables, along with presence-only records of three bumblebee species, were incorporated into the species distribution model. The results indicated that nearly 96% of the area (43 out of 45 cities in northern Pakistan) showed habitat suitability for all three species in the current scenario. Among these 43 cities, five exhibited a 100% overlap in suitable areas for the three species. However, this overlap area is expected to decrease in the future, particularly by the middle of the 21st century, highlighting these regions as prime candidates for conservation. In terms of bioclimatic factors influencing spatial distribution, the study found that temperature-related variables played a more significant role than precipitation-related ones in current and future scenarios. Specifically, bio3 (isothermality) contributed 48% to B. haemorrhoidalis and 43% to B. rufofasciatus, while bio2 (mean diurnal range) was the most influential factor for B. subtypicus. Temperature-related variables accounted for more than 80%, 69.4%, and 78.3% of the spatial variation in B. haemorrhoidalis, B. rufofasciatus, and B. subtypicus, respectively. This study demonstrates the critical influence of temperature on the spatial distribution of bumblebee species in northern Pakistan, underscoring the need for climate-focused conservation strategies to protect these important wild pollinators.